2013
DOI: 10.1242/jcs.118000
|View full text |Cite
|
Sign up to set email alerts
|

The human TREX-2 complex is stably associated with the nuclear pore basket

Abstract: SummaryIn eukaryotes, mRNA export involves many evolutionarily conserved factors that carry the nascent transcript to the nuclear pore complex (NPC). The THO/TREX complex couples transcription to mRNA export and recruits the mRNA export receptor NXF1 for the transport of messenger ribonucleoprotein particles (mRNP) to the NPC. The transcription and export complex 2 (TREX-2) was suggested to interact with NXF1 and to shuttle between transcription sites and the NPC. Here, we characterize the dynamics of human TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 57 publications
17
131
1
Order By: Relevance
“…This result provides a plausible explanation for the decreased levels of ATXN7L3 protein level observed after overexpression of ATXN7L3B (Fig. 3A and B), as previous studies have shown that ENY2 is necessary for stabilization of ATXN7L3 (17,20). Overexpression of ATXN7L3B likely sequesters ENY2, resulting in less ENY2-ATXN7L3 association and destabilization of ATXN7L3.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This result provides a plausible explanation for the decreased levels of ATXN7L3 protein level observed after overexpression of ATXN7L3B (Fig. 3A and B), as previous studies have shown that ENY2 is necessary for stabilization of ATXN7L3 (17,20). Overexpression of ATXN7L3B likely sequesters ENY2, resulting in less ENY2-ATXN7L3 association and destabilization of ATXN7L3.…”
Section: Resultssupporting
confidence: 68%
“…Examination of our MudPIT results indicates only a weak interaction of FH-ATXN7L3B with CETN2 (Fig. 1D), with no evidence for interaction with other TREX-2 components, including PCID2, DSS1, GANP, and CETN3 (20). We were not able to confirm interaction between ATXN7L3B and CETN2 by im-munoprecipitation, further suggesting that ATXN7L3B does not associate with TREX-2.…”
Section: Resultsmentioning
confidence: 74%
“…Tpr is thought to be the central architectural element of the nuclear basket (Krull et al, 2004) and is lately recruited during NPC reassembly (Bodoor et al, 1999;Haraguchi et al, 2000). Consistently, Nup153 localization to the NPC is not Tpr dependent (Frosst et al, 2002;Hase and Cordes, 2003), whereas the importance of Nup153 for Tpr recruitment is controversial: Nup153 depletion lead to a complete absence of Tpr from the NE on the one hand (Hase and Cordes, 2003), but not in other cases (Lussi et al, 2010;Mackay et al, 2010;Umlauf et al, 2013). In contrast to that, it is without any doubt that the association of Nup50 with NPCs necessitates the presence of Nup153 (Hase and Cordes, 2003;Mackay et al, 2010).…”
Section: Nup153 Assembly Into Nuclear Poresmentioning
confidence: 99%
“…In particular, the SAGA/TREX complex has been shown in both mammalian cells, Drosophila and nematodes to mediate transcriptional activation at the pores via interaction with nuclear basket proteins in a number of other organisms. 46,55,56 Third, since the X chromosome in hermaphrodites is 2-fold downregulated and not completely silent, two mechanisms linking DCC loading and transcriptional downregulation could be envisioned. In a first static scenario, the DCC remains stably associated with the X chromosome in hermaphrodites and does not allow association with nuclear pores, impairing transcriptional upregulation while allowing transcription.…”
Section: Open Questions and Considerations With The Modelmentioning
confidence: 99%